Understanding planform dynamics of the Ganga River in eastern part of India - Ashwini, Kumar; Pathan, Shehnaj Ahmed; Singh, Ajai (Spatial information research (Online), 2021)
To understand the natural processes of planform change, meandering and formation of braid bars, satellite sensor data of few decades play a significant role. The present research focuses on the planform dynamics of Ganga River from Sahibganj (Jharkhand) to Jalangi in West Bengal, India. This study is based on the sequential river planform maps. These maps were prepared using Landsat 1, Landsat 3, Landsat 4, Landsat 5 and Landsat 7 data for the period 1975–2015 at an interval of 5 years. The sinuosity index, braiding index and spatial analysis of maps were used to assess and classify the river into straight, braided and meander categories. This was observed that braiding index is continuously increasing and the meandering index has decreased from 1.6 to 1.24 during 1975 to 2015. The results showed the changes in channel migration with time and space. From the analysis, it is observed that the factors causing shifting of the Ganga River in some areas are natural and anthropogenic. Landsat images were found to be effective in determining the meandering index, braiding index and planform change of a river.